Eggs before chickens? Assessing Africa’s livestock revolution with an example from Ghana - Andam, Kwaw S.; Arndt, Channing; Hartley, Faaiqa (International Food Policy Research Institute, 2017)
This paper analyzes the impacts of adopting restrictive import policies for chicken meat in Ghana, which would be like the policies adopted in Nigeria. A prohibitive tariff stimulates domestic chicken meat production but also imposes significant costs on consumers and encourages illicit trade. However, a substantial poultry industry, producing mostly eggs, will exist independent of the border policy applied to chicken meat, due to the natural protection offered to local producers in the egg subsector. A subsector analysis of an egg production cluster in Ghana highlights the importance of trade links with other West African countries in developing the egg subsector. A focus on feed efficiency, through a mix of domestic production and imports, would benefit the layer industry, provide reasonable indications of prospects for globally competitive chicken meat production, and benefit other industries dependent on competitive feed, notably aquaculture.